2003
DOI: 10.1658/1100-9233(2003)014[0129:srasap]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Species richness, alien species and plant traits in Central Argentine mountain grasslands

Abstract: Pattern of native vegetation, distribution of alien species and variation of environmental parameters were studied in mountain grasslands in a lithologically homogeneous Córdoba mountain range in Central Argentina. CCA showed that altitude was the most important factor determining the compositional variation of the vegetation, with soil nutrient status and stoniness as additional factors. Short-grass communities, associated with the driest habitats on plateaus, showed higher small-scale native species richness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…At smaller scale the high herb species richness were also characterized by highest number of non-native species were similar to the findings of Cantero et al (2003) from central Argentine mountain grasslands. Thus these results do not favour the hypothesis of Elton (1958), which states, that areas of high species diversity prevent invasions (Robinson and Quinn 1988;Timmins and Williams 1991;Stohlgren et al 1999;Cantero et al 2003). Although most of the forest edges are highly invaded by Lantana camara (Raizada et al 2008).…”
Section: Resultssupporting
confidence: 82%
“…At smaller scale the high herb species richness were also characterized by highest number of non-native species were similar to the findings of Cantero et al (2003) from central Argentine mountain grasslands. Thus these results do not favour the hypothesis of Elton (1958), which states, that areas of high species diversity prevent invasions (Robinson and Quinn 1988;Timmins and Williams 1991;Stohlgren et al 1999;Cantero et al 2003). Although most of the forest edges are highly invaded by Lantana camara (Raizada et al 2008).…”
Section: Resultssupporting
confidence: 82%
“…Although the proportion of exotic species was relatively low compared with a study from Chile (Pauchard & Alaback 2004), it was higher than those recorded off‐roadsides in natural grassland communities (Pucheta et al . 1998; Cantero et al . 2003) and in the seed banks of the study area (Funes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, and despite three centuries of heavy grazing, these mesic mountain grasslands show a limited number of alien plant taxa both in standing vegetation (Pucheta et al . 1998; Cantero et al . 1999, 2003) and in seed banks (Funes et al .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies found that grassland species richness in Europe and N-America was reduced on soils with high moisture and nutrients, while attained maximum values at sites with relatively dry, nutrientpoor and shallow soils (reviews by Grace 1999 andby Keddy 2005; see also Bennie et al 2006;Bonanomi et al 2006;Maccherini 2006;Moeslund et al 2013b;Baumann et al 2016;Kleinebecker et al 2018;Palpurina et al 2019). Even in a different floristic kingdom, Cantero et al (2003) found that in mountain grasslands in Argentina, species richness of 1-m 2 quadrats had a negative relationship with soil depth and available water, and a positive correlation with stone cover. This is consistent with the classical model of humped-back relationship between productivity and richness, usually explained assuming that in very productive sites a few strong competitors will create closed canopies and accumulate litter, reducing the amount of light reaching soil surface and outcompeting stress-tolerant species that have lower growth rates (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%